An Exploration of Uzbekistan's Architectural History and its Promising Future (Genius Repository, 2023)
This scientific article delves into the rich architectural history of Uzbekistan, focusing on its distinctive indigenous heritage and the influences of various civilizations that have shaped its architectural landscape over centuries. It also highlights recent architectural developments and ongoing projects that demonstrate the country's commitment to preserving its architectural legacy while embracing modern trends. By examining Uzbekistan's architectural past and presenting an optimistic outlook, this article reveals a promising future for the nation's built environment.